From Kant to Foucault. What is there left of the copyright law? - Larochelle, Gilbert (Folia Philosophica, 2000)
The concept of „intellectual property”, in its modern sense, was formed in the 18th c. It is derived directly from the philosophy of subject (or, more precisely, from Kant’s and Fichte’s philosophy), from the conceptualisation of that subject’s status as „the author", and from recognising his work as a „commodity" in the commodity exchange. The legal distinction in question served then the purpose of establishing the normative and legal foundations of the copyright, which postulated a substantial connection between the book and the person of its creator. The critics, however, of modern institutions have completely demolished the above scheme. It is particularly the representatives of post-structuralism that defend the idea of a radical separation between the subject and the work. The present article attempts to answer the question: is plagiarism still possible in a world of ideas in which all possibility of identifying the work's origin, of distinguishing between a copy and the original, disappears? The theses advanced by Kante and Fichte and concerning the nature of the book have been here compared with Foucault’s position which denies the subject’s function as the author. Further on. the concept of responsibility for the text been cited as an idea that does not have to be seen from Kant's ontological perspective, and an attempt has been made to restore the subject to the environment of its work, and to show that the post-modern concept of the author remains impracticable.